Conversion of Mixed Waste Food Substrates by Carotenogenic Yeasts of Rhodotorula sp. Genus - Szotkowski, Martin; Plhalová, Žaneta; Sniegoňová, Pavlína; Holub, Jiří; Chujanov, Oleg; Špačková, Dominika; Blažková, Jana; Márová, Ivana (Microorganisms, 2023)
The consequence of the massive increase in population in recent years is the enormous production of mainly industrial waste. The effort to minimize these waste products is, therefore, no longer sufficient. Biotechnologists, therefore, started looking for ways to not only reuse these waste products, but also to valorise them. This work focuses on the biotechnological use and processing of waste oils/fats and waste glycerol by carotenogenic yeasts of the genus Rhodotorula and Sporidiobolus. The results of this work show that the selected yeast strains are able to process waste glycerol as well as some oils and fats in a circular economy model and, moreover, are resistant to potential antimicrobial compounds present in the medium. The best-growing strains, Rhodotorula toruloides CCY 062-002-004 and Rhodotorula kratochvilovae CCY 020-002-026, were selected for fed-batch cultivation in a laboratory bioreactor in a medium containing a mixture of coffee oil and waste glycerol. The results show that both strains were able to produce more than 18 g of biomass per litre of media with a high content of carotenoids (10.757 ± 1.007 mg/g of CDW in R. kratochvilovae and 10.514 ± 1.520 mg/g of CDW in R. toruloides, respectively). The overall results prove that combining different waste substrates is a promising option for producing yeast biomass enriched with carotenoids, lipids, and beta-glucans.
Keywords: waste frying oil; carotenoids; β-glucans; waste glycerol; lipids; waste animal fat; waste coffee oil; carotenogenic yeasts